The effect of block versus daily undulating periodization on strength and performance in adolescent football players - Gavanda, S.; Geisler, S.; Quittmann, O. J.; Schiffer, T. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Muscle mass, strength, and power are important factors for performance. To improve these characteristics, periodized resistance training is used. However, there is no consensus regarding the most effective periodization model. Therefore, the purpose of this study was to compare the effects of block (BLOCK) vs daily undulating periodization (DUP) on body composition, hypertrophy, strength, performance, and power in adolescent American football players. Methods: A total of 47 subjects participated in this study (mean [SD] age = 17 [0.8] y, strength training experience = 0.93 [0.99] y). Premeasurements and postmeasurements consisted of body mass (BM); fat mass; relative fat mass; fat-free mass (FFM); muscle mass (MM); muscle thickness of the vastus lateralis (VL), rectus femoris (RF), and triceps brachii (TB); 1-repetition-maximum back squat (BS) and bench press (BP); countermovement jump (CMJ); estimated peak power (Wpeak) from vertical jump performance; medicine-ball put (MBP); and 40-yd sprint. Subjects were randomly assigned in either the BLOCK or DUP group prior to the 12-wk intervention period consisting of 3 full-body sessions per week. Results: Both groups displayed significantly higher BM (P < .001), FFM (P < .001), MM (P < .001), RF (P < .001), VL (P < .001), TB (P < .001), BS (P < .001), BP (P < .001), CMJ (P < .001), Wpeak (P < .001), and MBP (P < .001) and significantly lower sprint times (P < .001) after 12 wk of resistance training, with no difference between groups. Conclusions: Resistance training was effective to increase muscle mass, strength, power, and performance in adolescent athletes. BLOCK and DUP affect anthropometric measures and physical performance equally.